REASONING ABILITY AMONG HIGHER SECONDARY STUDENTS - Kanimozhi, P.; Ganesan, P. (International Journal of Research -GRANTHAALAYAH, 2017)
The present study is a survey in nature to find out reasoning ability among higher secondary students in Madurai District. The investigator in order to find out reasoning ability among higher secondary students developed and validated a tool for the study. The tool is of a multiple choice type consisting of 50 items. The investigator selected a stratified random sample of 303 higher secondary students for the study. Data were collected from the sample. The data were given appropriate statistical treatments. The findings revealed that among higher secondary students 61.38 % of them are poor in reasoning ability, 21.45 % of them are average in reasoning ability, 16.5% of students are very poor in reasoning ability and only 0.66 % of students are good in reasoning ability. There exists a positive correlation between mathematical achievement and reasoning ability. There is no significant difference in reasoning ability among higher secondary students in terms of gender. It can be interpreted that both male and female students are uniform in reasoning ability.